Health, Technologies, and Politics in Post-Soviet Settings Navigating Uncertainties (Springer International Publishing, 2018)
This book uses a variety of empirical cases on topics including drug development, egg donation, and governance of healthcare facilities, to investigate how actors navigate the uncertainties that permeate the interfaces of health, technologies, and politics in post-Soviet settings and what the implications of their chosen navigation routes are. Contemporary societies are imbued with uncertainties, but the authors focus on settings where uncertainties multiply, making decisions, practises, and relations in everyday life precarious. Two worlds are brought into dialogue throughout the chapters of this book with the aim of facilitating mutual learning from one another - the world of science and technology studies (STS) and the high-income liberal democracies of the West, on one hand, and studies of post-socialism on the other. In so doing, this book encourages critical learning on ensuring the resilience of individual and societal health in situations of profound uncertainties. This timely collection will be of great interest to scholars, practitioners and policy makes in the fields of sociology, biomedicine, political science and public and global health.